Prospects of an online dispute resolution framework for Islamic Banks in Malaysia: An empirical legal analysis - Oseni, Umar A.; Omoola, Sodiq (Emerald, 2017)
Purpose This study aims to examine the prospects of using an online dispute resolution (ODR) platform for resolving relevant Islamic banking disputes in the usual banker–customer relationship in Malaysia. It is argued that through proper regulation, such innovative dispute management mechanism would not only address some legal risks associated with banking disputes but could also prevent reputational risks in the Islamic financial services industry.